(untitled) (Journal of Dentistry and Allied Science, 2024)
Bangladesh’s healthcare system has improved maternity, neonatal, child, and adolescent health, lowering mortality and improving well-being. The system still faces several challenges. This article covers Bangladesh’s healthcare system’s biggest difficulties, from infrastructure and medical specialists to accessibility and equity. The lack of regional design and devolutionary processes makes local community-specific healthcare plans hard to implement, mismatching central decisions with local reality. Misallocation of funds and materials makes it hard to offer essential healthcare. Lack of public health and management experience at district and upazila levels affects healthcare delivery quality, while political instability and lack of commitment have hampered healthcare project sustainability. Additionally, limited health information systems limit access to accurate and current data for decision-making. Despite these obstacles, this article suggests development areas. The healthcare workforce gap can be closed by investing more in healthcare training, especially in rural areas. A more comprehensive health information system that includes chronic noncommunicable diseases could improve healthcare planning and delivery. Encourage community empowerment and true community engagement for more effective and fair healthcare. Bangladesh’s healthcare system needs a comprehensive approach and commitment from governments and stakeholders. Focused actions and accountability and innovation can help the nation build a more comprehensive and inclusive healthcare system that supports all inhabitants. Journal of Dentistry and Allied Science, Vol. 7 No 1: 29-34